2016
DOI: 10.1177/0954409715618685
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of the in-service performance of a railway hydraulic damper

Abstract: In this study, an improved physical parametric model with key in-service parameters was established and experimentally validated for a high-speed railway hydraulic damper. A subtle variable oil property model was built and coupled into the full model to address the dynamic flow losses and the relief-valve system dynamics. Experiments were conducted to evaluate the accuracy and robustness of the full damper model and simulation, which determined the damping characteristics over an extremely wide range of excita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Ataei and Anaraki (2018) found that a leaked viscous damper must overcome the so-called "gap" phenomenon before it can engage in vibration control, and the gap will significantly alter the damping force. Wang et al (2017) and Huang and Zeng (2018) revealed that the air inside the hydraulic damper will degrade its dynamic stiffness and damping.…”
Section: Introductionmentioning
confidence: 99%
“…Ataei and Anaraki (2018) found that a leaked viscous damper must overcome the so-called "gap" phenomenon before it can engage in vibration control, and the gap will significantly alter the damping force. Wang et al (2017) and Huang and Zeng (2018) revealed that the air inside the hydraulic damper will degrade its dynamic stiffness and damping.…”
Section: Introductionmentioning
confidence: 99%